Performance of Pediatric Neuroradiologists Working from Home during a Pandemic at a Quaternary Pediatric Academic Hospital - Sher, A.C.; Salman, R.; Seghers, V.J.; Desai, N.K.; Sammer, M.B.K. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: As a result of the coronavirus disease 2019 (COVID-19) pandemic, many radiology departments shifted to working a portion of clinical assignments from home. To determine the effect of working from home on performance, productivity, quality, and safety, we evaluated turnaround time, volume of studies, and error rates on rotations worked from home compared with in the hospital.MATERIALS AND METHODS: The number of studies interpreted per day for each neuroradiologist, turnaround times, and error rates reported to peer learning was identified from April 1, 2020, through September 30, 2020. For each neuroradiologist, mean turnaround times and volumes per day at home versus in the hospital were compared. Similar comparison was performed for STAT studies.RESULTS: During the time period, 2597 CTs (1897 at home, 700 in the hospital) and 3685 MRIs (2601 at home, 1084 in the hospital) were read. By individual neuroradiologists, 57% (4/7) had shorter turnaround time at home and 57% (4/7) demonstrated an increase in the mean number of studies per day read at home. No statistically significant difference was noted in the neuroradiologists’ performance while reading STAT studies. Reported error rates were not found to be higher at home, with statistically significantly lower rates when working at home (P = .018).CONCLUSIONS: Variable productivity and performance of neuroradiologists when working from home versus in the hospital were found, being 57% faster and/or more productive while working at home without an increase in error rates. The decision to work at home versus in the hospital may best be based on local factors, balancing the variability among individual neuroradiologist’s and the institution’s needs, recognizing that working from home is not a one-size-fits-all phenomenon but requires adaptability for successful implementation.COVID-19coronavirus disease 2019SARS-CoV-2Severe Acute Respiratory Syndrome coronavirus 2STATstatimTATturnaround time